A comparative study of species diversity of migrant birds between protected and unprotected areas of the Hadejia-Nguru Wetlands, Nigeria - Ringim, AS; Magige, FJ; Jasson, RM (Tanzania Journal of Science, 2017)
Among the most complex and fascinating behaviour in birds is their long, non-stop migration. Despite Hadejia-Nguru Wetlands (Ramsar site) being an important wintering ground for migratory birds, little is known about the diversity while density is completely lacking. This study assessed the status of migratory birds in the wetland’s Protected Areas (PAs) and Unprotected Areas (UPAs). A total of 99 census points spaced 400 m apart with radius of 100 m were surveyed from 14 wetlands (48 point count stations in the PAs and 51 in the UPAs). A total of 54 migrant bird species belonging to 13 orders and 25 families were recorded. Of the 54 species, 20 were Intra-African migrants and 34 Palearctic winters including two globally threatened species; the European Turtle Dove Streptopelia turtur and Pallid Harrier Circus macrourus. Results showed that Protected wetlands had significantly higher species diversity (H' = 1.39) than Unprotected ones (H' = 1.28) (p = 0.0064), however, there was no significant difference in the density of birds between the two areas (p = 0.9246). The two areas were similar in species composition by 81%. Both Palearctic and Intra-Africa migrant birds were recorded in the wetland, thus revealing the importance of the Hadejia-Nguru as wintering sites for migratory birds. The Nigerian government has obligation to protect these migratory birds because it is a signatory to several international treaties aimed at conserving these birds. Key words: Circus macrourus, Hadejia-Nguru Wetlands, Threats to migratory ,birds Palearctic and Intra-Africa Migrant birds, Streptopelia turtur